The Caenorhabditis elegans mucin-like protein OSM-8 negatively regulates osmosensitive physiology via the transmembrane protein PTR-23. - Anne-Katrin Rohlfing; Yana Miteva; Lorenza Moronetti; Liping He; Todd Lamitina (PLoS Genetics)
The molecular mechanisms of animal cell osmoregulation are poorly understood. Genetic studies of osmoregulation in yeast have identified mucin-like proteins as critical regulators of osmosensitive signaling and gene expression. Whether mucins play similar roles in higher organisms is not known. Here, we show that mutations in the Caenorhabditis elegans mucin-like gene osm-8 specifically disrupt osmoregulatory physiological processes. In osm-8 mutants, normal physiological responses to hypertonic stress, such as the accumulation of organic osmolytes and activation of osmoresponsive gene expression, are constitutively activated. As a result, osm-8 mutants exhibit resistance to normally lethal levels of hypertonic stress and have an osmotic stress resistance (Osr) phenotype. To identify genes required for Osm-8 phenotypes, we performed a genome-wide RNAi osm-8 suppressor screen. After screening ~18,000 gene knockdowns, we identified 27 suppressors that specifically affect the constitutive osmosensitive gene expression and Osr phenotypes of osm-8 mutants. We found that one suppressor, the transmembrane protein PTR-23, is co-expressed with osm-8 in the hypodermis and strongly suppresses several Osm-8 phenotypes, including the transcriptional activation of many osmosensitive mRNAs, constitutive glycerol accumulation, and osmotic stress resistance. Our studies are the first to show that an extracellular mucin-like protein plays an important role in animal osmoregulation in a manner that requires the activity of a novel transmembrane protein. Given that mucins and transmembrane proteins play similar roles in yeast osmoregulation, our findings suggest a possible evolutionarily conserved role for the mucin-plasma membrane interface in eukaryotic osmoregulation.